2009
DOI: 10.1016/j.ejphar.2009.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nrf2 in prevention of high-fat diet-induced obesity by synthetic triterpenoid CDDO-Imidazolide

Abstract: The synthetic oleanolic triterpenoid 1-[2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oyl]imidazole (CDDO-Imidazolide or CDDO-Im) is an extremely potent activator of Nrf2 signaling. In cells undergoing adipogenesis, CDDO-Im prevents lipid accumulation in an Nrf2-dependent manner. However, in vivo evidence for effects of CDDO-Im on obesity is lacking. The goals of these studies were to determine if CDDO-Im can prevent high-fat diet-induced obesogenesis in the mouse, and to elucidate the molecular target of drug acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
217
4
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 254 publications
(237 citation statements)
references
References 21 publications
14
217
4
2
Order By: Relevance
“…In mice fed a high-fat diet, the bardoxolone methyl analogue CDDO-Im prevented increases in body weight, adipose mass, and hepatic lipid accumulation and increased energy expenditure. 51 These effects were not observed in Nrf2 knockout mice, suggesting that activation of Nrf2 has perceived positive effects on lipid and energy metabolism. Bardoxolone methyl-associated changes in body mass composition are being further evaluated in patients with type 2 diabetes and CKD.…”
Section: Discussionmentioning
confidence: 91%
“…In mice fed a high-fat diet, the bardoxolone methyl analogue CDDO-Im prevented increases in body weight, adipose mass, and hepatic lipid accumulation and increased energy expenditure. 51 These effects were not observed in Nrf2 knockout mice, suggesting that activation of Nrf2 has perceived positive effects on lipid and energy metabolism. Bardoxolone methyl-associated changes in body mass composition are being further evaluated in patients with type 2 diabetes and CKD.…”
Section: Discussionmentioning
confidence: 91%
“…The role of Nrf2 in regulating whole body weight and obesity has been investigated recently by our group and others. Oltipraz and oleanolic triterpenoid 1-[2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oyl] imidazole (CDDO-Im), two known activators of Nrf2, were shown to prevent HFD-induced increase of body weight, adipose mass and hepatic lipid accumulation [15,57] . Importantly, the effects of CDDO-Im were dependent on the Nrf2 system, while no such responses were observed in Nrf2-disrupted mice [57] .…”
Section: Role Of the Nrf2 System In Regulating Insulin Signaling Andmentioning
confidence: 99%
“…Recent studies revealed that Nrf2 also contributes to lipid metabolism (10,35). The genetic deletion of Nrf2 results in the rapid onset and progression of hepatic steatosis induced by a methionine-choline-deficient diet (3,46,56) and in differential gene expression of hepatic metabolism (49), while Nrf2 activation ameliorates high-fat diet-induced fatty liver (42).…”
mentioning
confidence: 99%